Applying KT Network Complexity to a Highly-Partnered Knowledge Transfer Effort; Comment on "Using Complexity and Network Concepts to Inform Healthcare Knowledge Translation" - JoAnn E. Kirchner; Sara J. Landes; Aaron E. Eagan (Kerman University of Medical Sciences, 2018)
The re-conceptualization of knowledge translation (KT) in Kitson and colleagues' manuscript "Using Complexity and Network Concepts to Inform Healthcare Knowledge Translation" is an advancement in how one can incorporate implementation into the KT process. Kitson notes that "the challenge is to explain how it might help in the healthcare policy, practice, and research communities." We propose that these concepts are well presented when considering highly-partnered research that includes all sectors. In this manuscript we provide an example of highly-partnered KT effort framed within the KT Complexity Network Theory. This effort is described by identifying the activities and sectors involved.